Effect of Diversified Model of Organizational Politics on Diversified Emotional Intelligence - Jamil Ahmad; Hafiz Muhammad Waqas Akhtar; Hifz ur Rahman; Rao Muhammad Imran; Noor ul Ain (Journal of Basic & Applied Sciences, 2017)
Purpose behind the study is to explore the influence of organizational politics of bankers on the ability based emotional intelligence and their diversified interplay. The sample of 292 bankers was used for testing organizational politics’ effect on emotional intelligence as well as individual and collective effect of facets of organizational politics (general political behavior, going along to get ahead, and pay and promotions policies) on dimensions of emotional intelligence (self and others’ emotional appraisal, use and regulation of emotions). The results witnessed that organizational politics significantly affects emotional intelligence, whereas organizational politics’ dimensions significantly predict each emotional intelligence dimension collectively. It is also noted that general political behavior and going along to get ahead have a negative effect on the dimensions of emotional intelligence. But pay and promotion policies positively influences emotional intelligence dimensions. The study can be helpful for the managers, who can identify the patterns of political behaviors and the persons who use it by openly discussing it with the employees through training. Limitations and future suggestions are presented in later part.